Pencegahan Hipertensi Dengan Senam Di Panti Pelayanan Sosial Lanjut Usia Sudagaran - prasanti adriani; Made Suandika; Noor Yunida Triana (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Hypertension was defined as an increase in systolic blood pressure of at least 140 mmHg or a diastolic pressure of at least 90 mmHg. Blood pressure will increase after the age of 45-55 years, arterial walls will experience thickening by a buildup of collagen substances in the muscle layer so that blood vessels will gradually narrow and become stiff. Gymnastics for the elderly is a light exercise and easy to do, not burdensome if applied to the elderly. The elderly social service is one of the nursing homes with its address at Sudagaran Village, Kalibagor District, Banyumas Regency. This orphanage cares for the elderly with a total of 34 people consisting of 11 grandparents and 23 grandmothers. The purpose of this community service is the prevention of hypertension through health education about healthy exercise, the implementation of exercise and the formation of a healthy exercise group for the prevention of hypertension in the elderly. There is a significant change before and after the training, namely good knowledge which was originally 5.8% increased to 91.2%, while knowledge that was less originally 79.5% decreased to 3%. This community service activity was attended by 34 people and got very good enthusiasm from the participants. This is evidenced by the number of questions from participants related to hypertension exercise that can improve the health of the elderly. Suggestions for future activities can be carried out by training the same activities in other place.